Veterans Treatment Courts: A Nationwide Review of Enacting and Eligibility State Statutes - Rapisarda, Sabrina S. (Victims & offenders, 2024)
Veterans Treatment Court (VTC) is the fastest growing type of treatment court in the United States with over 600 VTCs in operation today. Despite this recent proliferation, minimal scholarship has been conducted investigating how the state-level statutory landscape influences VTCs. The current study begins to address this gap by comprehensively reviewing and analyzing state legislation that governs the enactment, operation, and eligibility requirements of VTCs nationwide. Our initial search reveals that 70% of states currently operating VTCs are statutorily authorized at the state-level, of which nearly two-thirds also enumerates operational and eligibility criteria, such as military status and branch, mental health diagnosis, the “nexus,” criminal history, military discharge status, offense severity and type, and more. Our analysis indicates considerable variation and nuance across states but coalesced into several unifying themes. The results provide insights on one of the many important powers involved in shaping the operational and eligibility elements of VTCs – state legislatures – and can serve as a catalyst for future research on the myriad factors involved in determining how we conceptualize VTCs are and who is included in them.